2018
DOI: 10.1093/fampra/cmy043
|View full text |Cite
|
Sign up to set email alerts
|

Becoming frail: a major turning point in patients’ life course

Abstract: Becoming frail is a major turning point in patients' life course. Coordinated multiprofessional management that takes account of patients' perceptions could help in negotiating a feasible care plan adapted to the patient's needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…A similar knowledge gap was cited in a qualitative study of HCPs and frailty in the UK 21 . While mixed views were expressed about frailty terminology among HCPs and patients, in agreement with the literature, the majority of participants expressed a strong aversion to the dialogue of frailty [22][23] . One participant suggested that frailty terminology may be misjudged by clinicians if not universally understood.…”
Section: Discussionsupporting
confidence: 57%
“…A similar knowledge gap was cited in a qualitative study of HCPs and frailty in the UK 21 . While mixed views were expressed about frailty terminology among HCPs and patients, in agreement with the literature, the majority of participants expressed a strong aversion to the dialogue of frailty [22][23] . One participant suggested that frailty terminology may be misjudged by clinicians if not universally understood.…”
Section: Discussionsupporting
confidence: 57%
“…Primary studies included in review (n =8) a specific health event/turning point (e.g., stroke or fall), which caused persons to cross a threshold and become "frail" (Escourrou et al, 2017(Escourrou et al, , 2019Skilbeck et al, 2018). Once persons were living with frailty, participants perceived that further decline would follow (Grenier, 2006).…”
Section: Narrative Summary Of Themesmentioning
confidence: 99%
“…Once persons were living with frailty, participants perceived that further decline would follow (Grenier, 2006). The process of "becoming frail" was described as an inevitable part of the aging process (Age UK, British Geriatrics Society, 2015; Escourrou et al, 2017Escourrou et al, , 2019Grenier, 2006Grenier, , 2007Puts et al, 2009;Schoenborn et al, 2018;. A participant explained, "Frailty is not something that you can prevent, you cannot do anything, it just happens when you get older" (Puts et al, 2009, p. 264).…”
Section: Narrative Summary Of Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…The FRAIL predicts poor outcomes to a similar extent as the Fried et al (5) questionnaire and the Rockwood frailty screens (9). Becoming frail marks a major downhill slide in older persons and if identified early before the onset of disability, frailty is potentially reversible (10,11).…”
mentioning
confidence: 86%